Pulsations in Evolved Massive Stars - Kraus, Michaela (2019)
The post-main sequence evolution of massive stars still bears many unknowns. In particular, the physical processes involved in triggering enhanced mass-loss or eruptions are yet to be established. In this Chapter, the post-main sequence evolution of massive stars, and the various phases which are well-known for their mass ejections, are briefly touched upon. Amongst those transition phases, two classes of objects are discussed in more detail: the B-type supergiants and the Yellow Hypergiants. Their ability to perform pulsations is presented based on observational and theoretical evidences. Moreover, the possibility of a pulsation-mass-loss relation in these two classes of objects is delineated.